Low doses of 3-phenyl-lawsone or meglumine antimoniate delivery by tattooing route are successful in reducing parasite load in cutaneous lesions of Leishmania (Viannia) braziliensis-infected hamsters - Meira, Rafaella de Miranda Villarim; Gomes, Sara Lins da Silva; Schaeffer, Edgar; Da Silva, Thayssa; Brito, Andréia Carolinne de Souza; Siqueira, Larissa Moreira; Inácio, Job Domingos; Almeida-Amaral, Elmo Eduardo; Da-Cruz, Alda Maria; Bezerra-Paiva, Milla; Neves, Renata Heisler; Rodrigues, Luciana Silva; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Current therapeutic ways adopted for the treatment of leishmaniasis are toxic and expensive including parasite resistance is a growing problem. Given this scenario, it is urgent to explore treatment alternatives for leishmaniasis. The aim of this study was to evaluate the effect of 3-phenyl-lawsone (3-PL) naphthoquinone on Leishmania (Viannia) braziliensis infection, both in vitro and in vivo, using two local routes of administration: subcutaneous (higher dose) and tattoo (lower dose). In vitro 3-PL showed low toxicity for macrophages (CC50 >3200 µM / 48h) and activity against intracellular amastigotes (IC50 = 193 ± 19 µM / 48h) and promastigotes (IC50 = 116 ± 26 µM / 72h), in which induced increased ROS generation. Additionally, 3-PL up-regulated the production of cytokines such as tumor necrosis factor alpha (TNF-α), monocyte chemotactic protein 1 (MCP-1), interleukin-6 (IL-6) and IL-10 in infected macrophages, however, the anti-amastigote action was independent of nitric oxide production. Treatment of hamsters infected with L. (V.) braziliensis from one week after infection with 3-PL by subcutaneous (25 µg/Kg) or tattooing (2.5 µg/Kg) route, during 3 weeks (3 times/week) or 2 weeks (2 times/week) significantly decreased the parasite load (p<0.001) in the lesion. The reduction of parasite load by 3-PL treatment was comparable to reference drug meglumine antimoniate administered by the same routes (subcutaneous 1mg/Kg and tattoo 0.1mg/Kg). In addition, treatment started from five weeks after infection with 3-PL per tattoo also decreased the parasite load. These results show the anti-leishmanial effect of 3-PL against L. (V.) braziliensis and its efficacy by subcutaneous (higher dose) and tattoo (lower dose) routes. In addition, this study shows that drug delivery by tattooing the lesion allows the use of lower doses than the conventional subcutaneous route, which may support the development of a new therapeutic strategy that can be adopted for leishmaniasis.